2019
DOI: 10.3758/s13423-019-01580-2
|View full text |Cite
|
Sign up to set email alerts
|

The motor system’s [modest] contribution to speech perception

Abstract: Recent evidence suggests that the motor system may have a facilitatory role in speech perception during noisy listening conditions. Studies clearly show an association between activity in auditory and motor speech systems, but also hint at a causal role for the motor system in noisy speech perception. However, in the most compelling "causal" studies performance was only measured at a single signal-to-noise ratio (SNR). If listening conditions must be noisy to invoke causal motor involvement, then effects will … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 86 publications
4
36
0
Order By: Relevance
“…Overall, this more recent research has coalesced around analysis-by-synthesis (Bever, 2010;Skipper, Nusbaum, & Small, 2005) and Bayesian inference (Moulin-Frier, Diard, Schwartz, & Bessière, 2015) frameworks in which heard (or seen) speech is, at some level, re-encoded in articulatory terms to generate perceptual hypotheses that constrain the analysis and interpretation of incoming speech sounds. While several researchers have dismissed the notion that such mechanisms are a core component of speech perception Holt & Lotto, 2008;Rogalsky et al, 2020;Scott, McGettigan, & Eisner, 2009;Venezia & Hickok, 2009), it has been acknowledged that motor speech circuits likely play a small, modulatory role in certain listening situations (Stokes, Venezia, & Hickok, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this more recent research has coalesced around analysis-by-synthesis (Bever, 2010;Skipper, Nusbaum, & Small, 2005) and Bayesian inference (Moulin-Frier, Diard, Schwartz, & Bessière, 2015) frameworks in which heard (or seen) speech is, at some level, re-encoded in articulatory terms to generate perceptual hypotheses that constrain the analysis and interpretation of incoming speech sounds. While several researchers have dismissed the notion that such mechanisms are a core component of speech perception Holt & Lotto, 2008;Rogalsky et al, 2020;Scott, McGettigan, & Eisner, 2009;Venezia & Hickok, 2009), it has been acknowledged that motor speech circuits likely play a small, modulatory role in certain listening situations (Stokes, Venezia, & Hickok, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Recall that these tasks are known to dissociate, as mentioned above.) Motor stimulation significantly increased errors only for the sublexical task, resulting in between 5-10% change in accuracy under noisy conditions, which approximates a 1 dB size effect (Stokes et al, 2019). The effects of motor stimulation during word comprehension affected only reaction times but not accuracy.…”
Section: Introductionmentioning
confidence: 64%
“…Accordingly, the research questions are becoming more nuanced as well, with an aim toward quantifying the magnitude of motor influence and specifying the condition(s) under which it holds (Skipper et al, 2017). For example, Stokes et al (2019) used a behavioral psychometric approach to estimate the effect size of motor interference (articulatory suppression) on minimal pair perception in noise. They reported that motor interference reduced speech perception under noisy conditions by an average of approximately 1 dB, which is to say that increasing the stimulus volume by just 1 dB was enough to overcome the perceptual decrement of motor suppression.…”
Section: Introductionmentioning
confidence: 99%
“…These routes are thought to participate in acoustic/phonological transcoding (Catani et al, 2005). The recurrent motor-perceptual interaction is known to facilitate speech perception of unfamiliar speech stimuli, e.g., distorted speech and novel or low-frequency words (Wu et al, 2014;Stokes et al, 2019). Therefore, greater involvement of the entire perisylvian network into the APW compared to the NPW response in our experiment may indicate that newly learned semantic association boosted perceptual processing of incoming novel linguistic stimuli.…”
Section: Semantic Learning Effectsmentioning
confidence: 76%